2021
DOI: 10.22214/ijraset.2021.34241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Logistic Regression and Decision Tree method for Credit Card Fraud Detection

Abstract: The use of Credit cards has drastically increased as they become one of the vital and most used modes of payment. Along with this the Credit Card. Fraud has also grown to a greater extent. Thus, it becomes vital for Credit card companies or banks to identify fraudulent transactions. Machine learning algorithms are used to analyze and identify suspicious transactions. Credit Card Fraud detection is a typical case of classification and data analysis, in this, we have focused on analyzing and comparing the data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This study achieved the best prediction performance result. [35] Logistic Regression 77.97% [36] Logistic Regression 99.26% [37] Logistic Regression 91.20% [38] Logistic Regression 74.65% This study Logistic Regression 99.88%…”
Section: Experimental Analysis and Presentation Of The Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This study achieved the best prediction performance result. [35] Logistic Regression 77.97% [36] Logistic Regression 99.26% [37] Logistic Regression 91.20% [38] Logistic Regression 74.65% This study Logistic Regression 99.88%…”
Section: Experimental Analysis and Presentation Of The Resultsmentioning
confidence: 91%
“…The accuracy results of this study were compared with similar studies that used LR to detect fraudulent credit card transactions, as shown in Table II. The study in [35] used a credit card transaction dataset from the UCI Machine Learning Data Repository to detect frauds in credit card transactions, while studies [36][37][38] used the same dataset as this study. All these studies used the LR method to achieve high accuracy and predictive performance, regardless of their individual approaches.…”
Section: Experimental Analysis and Presentation Of The Resultsmentioning
confidence: 99%